A Correlational Analysis of Student Achievement in Socioeconomic Disparities - Kusumo Hadi Santoso (Universitas PGRI Ronggolawe Tuban, 2024)
This study investigates the correlation between socioeconomic status (SES) and student academic achievement in Bektiharjo Village, Indonesia, comprising both urban and rural settings. Utilizing a quantitative survey design, data were gathered from 50 junior high school students, examining key SES indicators such as parental education and family income. The results reveal a statistically significant relationship between SES and academic performance, with higher parental education levels and family income positively influencing student outcomes. This study underscores the critical impact of socioeconomic disparities on educational attainment and highlights the need for targeted interventions to promote educational equity. The findings contribute to the theoretical understanding of social and cultural capital in education and offer practical implications for policymakers and educators to develop inclusive strategies that address these disparities, fostering a more just and equitable education system.